Non-conventional potentials in the contemporary graphic design: A LULULUX case study - Paes, Gilherme Paranhos; Oliveira, Mirtes Marins de; Carvalho, Agda Regina de (DAT Journal, 2020)
This article aims to analyze the graphic project called LULULUX (2014), realized by the Brazilian graphic designer Gustavo Piqueira. LULULUX is a narrative on a dinner set where the Piqueira uses as support napkins, cup holders and placemats as a book’s proposition. The project points to the limits of the printed book, both in its materiality as well as its visual compositions and functions, generating a parallel and a questioning about the conventionality of contemporary editorial design, exposing new perspectives and strengths for the printed book in a possibility of an object material of great narrative and conceptual value.